Residual Cdk1/2 activity after DNA damage promotes senescence - Müllers, Erik; Silva Cascales, Helena; Burdova, Kamila; Macurek, Libor; Lindqvist, Arne (Aging cell, 2017)
In response to DNA damage, a cell can be forced to permanently exit the cell cycle and become senescent. Senescence provides an early barrier against tumor development by preventing proliferation of cells with damaged DNA. By studying single cells, we show that Cdk activity persists after DNA damage until terminal cell cycle exit. This low level of Cdk activity not only allows cell cycle progression, but also promotes cell cycle exit at a decision point in G2 phase. We find that residual Cdk1/2 activity is required for efficient p21 production, allowing for nuclear sequestration of Cyclin B1, subsequent APC/CCdh1 -dependent degradation of mitotic inducers and induction of senescence. We suggest that the same activity that triggers mitosis in an unperturbed cell cycle enforces senescence in the presence of DNA damage, ensuring a robust response when most needed.
Keywords: stárnutí buněk; Cyclin-Dependent Kinase Inhibitor p21; cyklin-dependentní kinasa 2; Cdk2; poškození DNA; checkpoint recovery; osteoblasty; viabilita buněk; Purines; Single-Cell Analysis; Antigens, CD; Cdk1; kadheriny; cell cycle; CD antigeny; Cyclin B1; Humans; Retinal Pigment Epithelium; DNA Damage; Thiazoles; Epithelial Cells; Etoposide; analýza jednotlivých buněk; etoposid; p21; thiazoly; Quinolines; Osteoblasts; Gene Expression Regulation; retinální pigmentový epitel; senescence; Cadherins; kontrolní body fáze G2 buněčného cyklu; cyklin B1; Pteridines; epitelové buňky; pteridiny; regulace genové exprese; proteinkinasa CDC2; Cell Line; Cellular Senescence; DNA damage response; chinoliny; CDC2 Protein Kinase; Cell Line, Tumor; nádorové buněčné linie; puriny; G2 phase; velikost buňky; Cyclin-Dependent Kinase 2; G2 Phase Cell Cycle Checkpoints; Cell Survival; lidé; Signal Transduction; inhibitor p21 cyklin-dependentní kinasy; buněčné linie; signální transdukce; Cell Size